Biological flow in large vessels : dialog between numerical modeling and in vitro/in vivo experiments /: dialog between numerical modeling and in vitro/in vivo experiments. (2022) - Deplano, Valérie; Fullana, José-Maria; Verdier, Claude
No abstract available